Designing a phononic crystal with a defect for target frequency matching using an analytical approach. Issue 17 (5th July 2022) - Jo, Soo-Ho; Youn, Byeng D.
Abstract: This paper proposes a one-dimensional, defect-introduced phononic crystal design for target frequency matching. A quarter-wave stack is used as a unit cell. The supercell-technique-based transfer matrix method enables the defect's length to be explicitly derived; this generates a defect band at the target frequency in band-structure analysis. For the verification through time-harmonic analysis, the perturbation-theory-incorporated S-parameter method is used. The results show that the proposed design enables the realization of defect-mode-induced energy localization at the desired frequency, regardless of the harmonic number, supercell size, and defect location. The proposed design is validated by numerical examples through the finite element method.